A facile strategy to generate polymeric nanoparticles for synergistic chemo-photodynamic therapy1. Issue 20 (11th March 2015) - Deng, Xin; Liang, Yan; Peng, Xinyu; Su, Ting; Luo, Song; Cao, Jun; Gu, Zhongwei; He, Bin
<x xml:space="preserve">Abstract</x> Polymeric nanoparticles generated by mPEG-tetrakis(4-carboxyphenyl)porphyrin amphiphiles were used to trap doxorubicin for synergistic chemo-photodynamic therapy.